Dynamic mechanical properties of bio-polymer graphite thin films - Kamarudin, M.Saddam; M. Rus, Anika Zafiah; Abdullah, Nur Munirah; Abdullah, M. F. L (IOP Publishing, 2017)
Waste cooking oil is used as the main substances in producing graphite biopolymer thin films. Biopolymer is produce from the reaction of bio-monomer and cross linker with the ratio of 2:1 and addition of graphite with an increment of 2% through a slip casting method. The morphological surface properties of the samples are observed by using Scanning Electron Microscope (SEM). It is shown that the graphite particle is well mixed and homogenously dispersed in biopolymer matrix. Meanwhile, the mechanical response of materials by monitoring the change in the material properties in terms of frequency and temperature of the samples were determined using Dynamic Mechanical Analysis (DMA). The calculated cross-linked density of biopolymer composites revealed the